Eosinophils - Williams, Tim (Henry Stewart Talks, 2009)
White blood cell containing granules staining pink with eosin and a bilobed nucleus, Specialised for defence against worm infection, Accumulate in high numbers in lungs of allergic asthmatic patients, Also involved in hay fever, allergic eczema etc, Induce tissue damage and organ dysfunction when inappropriately activated, Interleukin-5 (IL-5) important for eosinophil production in bone marrow, Anti-IL-5 antibodies suppress circulating eosinophil numbers, Eotaxin is a chemoattractant protein involved in recruiting eosinophils to the lung, Small molecule antagonists have been developed to block the Eotaxin receptor, CCR3, as potential therapeutic compounds
Reviewed at 2020/05/01